The Work of Student’s Nervousness in Learning English - Mohammad Amiruddin; Evha Nazalatus Sa'adiyah Sy; Muh. Darrin Zuhri (Journey: Journal of English Language and Pedagogy, 2023)
The purpose of this study is to investigate the role of students' anxiousness in studying English at Madura University. The population consists of English Department students. This study employs an ex-post facto research method, using a quantitative approach; it emphasizes how past behavior might be used to anticipate future events. The sample approach is proportional stratified random sampling. To analyse the data, a simple regression approach was applied. The study's findings reveal that the percentage of students who are anxious about studying English at Madura University's English Department is not very high, at 0.64 (64%). The degree of anxiety among students affects their ability to produce English. those with low levels of anxiety will do better in English than those with high levels of anxiety. It indicates that teachers should give and support students with a pleasurable and exciting language environment in order to reduce their stress in language learning. It is required that academic society members, particularly those who are receptive to students' apprehension, emotional condition, and motivation in language acquisi